CTJ: Input-output based relation combinatorial testing strategy using Jaya algorithm - Ng, Yeong Khang (2019)
Software testing is a vital part in software development lifecycle. Most of the time, system under test has more than one input and testing of every combinations of inputs is almost impossible as the time of execution of test case is outrageously long. Combinatorial testing is the way to encounter exhaustive testing through the testing of every input values and every combination between parameters. Combinatorial testing can be divided into three types which are uniform strength interaction, variable strength interaction and input-output based relation (IOR). IOR combinatorial testing only test for the important combinations that selected by tester. Most of the researches in combinatorial testing applied uniform and variable interaction strength but there are only few studies feature IOR. Thus, IOR combinatorial testing is selected to be studied in this research. To overcome the combinatorial optimization problem, Jaya algorithm is proposed to apply in this project since metaheuristic algorithm is fast in optimization and this strategy is named as CTJ. The result of applying Jaya algorithm in input-output based combinatorial testing is acceptable since it produces nearly optimum number of test cases in the satisfactory time range.